SLOSH-study The Swedish Longitudinal Occupational Survey of Health - SLOSH - 2012 - Westerlund, Hugo (Stockholm University, 2015)
The Swedish Longitudinal Occupational Survey of Health (SLOSH) is a unique prospective study on work environment and health. SLOSH was initiated by the Stress Research Institute at Stockholm University in 2006 and aims to study the complex relationships between work organization, work environment, labour market participation and health.

Commissioned by Stress Research Institute, Statistics Sweden (SCB) mails self-completion questionnaires to the participants every second. Registry data are linked both retrospectively and prospectively.

SLOSH is based on the Swedish Work Environment Surveys of 2003 and 2005 (SWES). The first follow-up was conducted in March 2006, when all the 9,200 participants of the SWES 2003 were mailed self-completion questionnaires. In 2008, the second follow-up was realized, where also participants of the 2005 SWES were invited to participate. The core of the SLOSH therefore consists of a total of 18 915 persons. The third follow-up was conducted in 2010, which also included 2,553 participants from Stockholm and Västra Götaland who has responded to SWES 2007, a fourth follow-up in 2012, and a fifth data collection during spring 2014. Continued follow-ups are planned for every other year.
The survey is available in two versions, one for participants in gainful employment and one for those who are not gainfully employed or work more than 30 percent. The survey for those in gainful employment is divided into three parts with the first part containing questions from SWES, but also new questions about changes in employment, demand and control at work, effort and reward, organizational justice, leadership etc. The second part is about health and wellbeing and the third section highlights the general life situation. Also the survey for those who have temporarily or permanently left the labour market is divided into three parts, where the second and third part is almost identical to the survey for workers. The first part deals with questions about current supply, reasons why for not working and the positive and negative aspects of not being gainfully employed. In order not to burden the participants with too many questions, questionnaire data is linked to register data on employment, sick leave, hospitalisation etc. both prospectively and back in time.

Purpose:

SLOSH is a unique prospective study on work environment and health. It is expected to provide a basis for improvements of work environment and to contribute to a better understanding regarding work-related ill-health in Sweden and other countries.

During spring 2012, a fourth follow-up was conducted. The follow-up included those who participated in the Swedish Work Environment Surveys of 2003 and 2005 (SWES). The sample consisted of 17,409 individuals. A total of 9880 respondents answered to one of the two questionnaires that was sent out, with a response rate of 56,8 percent.
7,325 respondents answered the questionnaire for working persons, and 2,555 answered the questionnaire for non-working persons.

Studien Swedish Longitudinal Occupational Survey of Health (SLOSH) är en longitudinell studie som påbörjades under 2006 av Stressforskningsinstitutet på Stockholms universitet.

Studien förväntas ge underlag till ett effektivare arbetsmiljöarbete och till en ökad förståelse av den arbetsrelaterade ohälsan i Sverige. Dessutom är syftet att bidra till den vetenskapliga kunskapen om hur arbetslivet, i kombination med faktorer utanför arbetet, påverkar människans hälsa. Med studiens longitudinella upplägg, som innebär att samma personer följs med liknande frågor över tid, ges möjligheter att analysera vad som kommer först i en tänkt orsakskedja.


På uppdrag av Stressforskningsinstitutet skickar SCB ut postenkäter vartannat år. Registerdata från register om bland annat sjukskrivning och sjukhusinläggning kopplas till svaren både retrospektivt (bakåt i tiden) och prospektivt (framåt i tiden).


SLOSH bygger på 2003, 2005 och delvis 2007 års arbetsmiljöundersökningar (AMU).
I mars 2006 gjordes en första uppföljning av de 9 200 personer som hade besvarat AMU 2003 genom att frågeformulär skickades ut per post. Under 2008 genomfördes den andra uppföljningen, då även de som hade besvarat 2005 års AMU inbjöds att medverka. Kärnan i SLOSH består därför av totalt 18 915 personer. Under 2010 genomfördes en tredje uppföljning där även 2 553 deltagare från AMU 2007 bosatta i Stockholms eller Västra Götalands län inbjöds att delta. Under 2012 genomfördes en fjärde insamling och under våren 2014 en femte. Därefter planeras insamling att ske vartannat år.
Enkäten som skickas med post till deltagarna finns i två versioner, en för dem som förvärvsarbetar och en för dem som inte förvärvsarbetar. Enkäten för förvärvsarbetande innehåller frågor om arbetsorganisation, arbetsmiljö, livsstil, social situation utanför arbetet samt hälsa. Enkäten till icke förvärvsarbetande liknar den för förvärvsarbetande, men istället för frågor om arbetet ställs frågor som kan vara relevanta för ålderspensionärer, helt förtidspensionerade, arbetslösa, studerande, långtidssjukskrivna, föräldralediga, hemarbetande och andra som tillfälligt eller permanent slutat att förvärvsarbeta.

Syfte:

SLOSH är en unik longitudinell studie om arbetslivets förändringar, arbetsmiljö, stress och välbefinnande. Studien förväntas ge underlag till ett effektivare arbetsmiljöarbete och till ökad förståelse gällande den arbetsrelaterade ohälsan i Sverige och övriga världen.

Under våren 2012 genomfördes en fjärde uppföljning i SLOSH-studien. Urvalet bestod av 17 409 personer efter det att övertäckningen och personer som tidigare meddelat att de inte kan/vill delta räknats bort. Det var totalt
9 880 personer som besvarade någon av de två frågeblanketterna som skickades ut, vilket motsvarade 56,8 procent av urvalet. Det var 7 325 personer som valde att svara på blanketten till förvärvsarbetande och 2 555 personer som
valde att svara på blanketten till de som inte förvärvsarbetar.
SLOSH-studien The Swedish Longitudinal Occuptional Survey of Health - SLOSH - 2012
Keywords: occupations; yrken; job characteristics; arbetskaraktäristika; labour and employment; arbete och sysselsättning; workloads; arbetsbörda; sick leave; sjukfrånvaro; part-time employment; deltidsarbete; temporary employment; tillfällig anställning; personnel; personal; Cohort Studies; Kohortstudier; Workload; Arbetsbelastning; Workplace; Arbetsplats; Task Performance and Analysis; Uppgiftsprestation och analys; Psychology, Industrial; Arbetspsykologi; Job Satisfaction; Arbetstillfredsställelse; Public Health; Folkhälsa; early retirement; förtidspensionering; retirement; pensionering; termination of service; uppsägning; unemployed; arbetslösa; full-time employment; heltidsarbete; hours of work; arbetstid; REWHARD; REWHARD; HEALTH; HÄLSA; Working conditions; Arbetsförhållanden; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin